Respiratory and Rehabilitation Expert Consensus on Full-Cycle Rehabilitation Assessment and Treatment for Elderly Patients with Chronic Obstructive Pulmonary Disease - CHEN Xin; JIA Jie; DING Yipeng; YE Xujun; DONG Anqin; HE Jing; LIAO Weijing; ZHENG Jiejiao; YU Binbin; CHEN Zuobing; FANG Yuan; YAO Liqing; et al. (康复学报)
Chronic obstructive pulmonary disease (COPD) is one of the major chronic airway diseases, with the highest prevalence among individuals over 60 years old, significantly impacting the health of elderly patients. Guidelines of prevention and treatment for COPD in domestic and abroad recommend pulmonary rehabilitation as a complementary and effective adjunct to pharmacological treatment. Pulmonary rehabilitation can significantly improve patients' respiratory function and physical fitness, alleviate symptoms, reduce hospitalization and mortality rates. However, the specific contents of pulmonary rehabilitation for elderly patients with COPD in different stages were different. This expert consensus elaborates on the assessment and treatment methods of pulmonary rehabilitation for elderly patients with COPD in the acute exacerbation stage, post-exacerbation remission stage and outpatient stable stage, aiming to provide guidance for pulmonary rehabilitation treatment at different stages of COPD. This expert consensus identifies common functional impairments of elderly patients with COPD, including respiratory dysfunction, exercise tolerance impairment, psychological issues, swallowing dysfunction and cognitive impairment. It recommends a comprehensive assessment for multifaceted impairments of elderly patients with COPD based on the International Classification of Functioning, Disability and Health (ICF) framework from four aspects including body structure, body function (respiratory function, cardiac function, motor function, psychological and cognitive function, swallowing function, and nutritional factors), activity and participation, and environmental factors. Pulmonary rehabilitation is suitable for all patients with relevant symptoms of COPD and/or those at high risk of acute exacerbations (high-level evidence). The rehabilitation team, treatment plan, and treatment location should be adjusted in time as the condition evolves and changes, to establish a full-cycle rehabilitation. Smoking cessation is a crucial intervention to slow down the decline of lung function and the progression of COPD (high-level evidence). Through adequate nutritional support, elderly patients with COPD can improve nutritional status, and enhance physical strength and quality of life, so as to better manage the disease and promote rehabilitation (low to moderate-level evidence). Oxygen therapy is recommended for patients with advanced COPD who remain hypoxemic at rest (low to moderate-level evidence). Some emerging rehabilitation treatments (such as neuromuscular electrical stimulation, acupuncture and certain traditional Chinese medicines) may be beneficial for elderly patients with COPD (low to moderate-level evidence). Rehabilitation treatment process was divided into phase Ⅰ, phase Ⅱ and phase Ⅲ of pulmonary rehabilitation based on the different stages of elderly patients with COPD in this expert consensus. It further details the target population, implementation location, rehabilitation content, assessment content, participating disciplines and rehabilitation goals for each phase in the rehabilitation process. The consensus emphasizes that multidisciplinary personnel, including clinical respiratory specialists, primary care physicians, rehabilitation physicians/therapists, nurses, nutritionists, psychiatrists/psychologists and social workers should actively coordinate and collaborate in the full-cycle rehabilitation process for elderly patients with COPD.